Improving the Quality of Islamic Education for Early Childhood through the Role of the Family - Syukron Jazuli (Al-Bustan: Jurnal Pendidikan Islam, 2025)
This research aims to analyse the role of the family in improving the quality of Islamic religious education for early childhood. Through a qualitative approach with a literature study method, this research examines how parents and other family members form an environment that supports early learning of Islam. The researcher collected information and data from various relevant written sources, such as books, journal articles, research reports, and other sources related to this topic. The results show that the role of the family in Islamic religious education is very significant, especially in providing examples, habituation, and the introduction of Islamic values from an early age. With parents' active involvement in teaching daily worship and guiding morality according to Islamic teachings, children tend to show a better understanding of religious values and Islamic behaviour. This study suggests the need for a mentoring programme for families in early childhood religious education to strengthen the synergy between families and educational institutions.